Handle decompositions of simply-connected five-manifolds. II - Shkol’nikov, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Handle decompositions of simply connected smooth or piecewise linear five-manifolds are considered. The basic notions and constructions necessary for proving further results are introduced.